Correlation Family Support on Independence of Patients Schizophrenic Activities Daily Living (ADL) - Ronal Surya Aditya (Journal of Global Pharma Technology, 2020)
Family support for schizophrenics has proven to be very effective in supporting patients' healing and independence. And this program has been widely recommended by several minimum service standards published internationally. However, the reality is that the family is not yet fully supported, even though good family support can increase patient independence. Aims to find out the relationship between family support and ADL independence in schizophrenia patients. The research design used in this study was a correlation method that used a cross-sectional approach, with samples in this study were 70 family members with schizophrenia. The variables in this study are family supports (instrumental, informational, appreciation, assessment). Based on the results of statistical tests using the Spearman Rank shows ρ value for instrumental family support (0.020), informational family support (0.031), family support award (0.021), and family support assessment (0.021). Full family support is necessary and given to sufferers, especially schizophrenics. Comprehensive family support can be given if the caregiver is a member of the nuclear family who has a good psychological closeness with the sufferer. The results of this study can explain future approaches to dealing with the family support of schizophrenia patients Keywords: ADL Independence, Family Support, Schizophrenia.